A Study of Three-Level Neutral Point Clamped Inverter Topology - Muhammad Kashif; Zhuo Fang; Samir Gautam; Yu Li; Ali Syed (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The three-level Neutral Point Clamped (NPC) inverter has become matured and widely used topology in high-power medium-voltage applications due to several advantages associated with it as compared to other available multilevel topologies. This paper presents a brief review on operation of three-level NPC inverter. Different modulation strategies used in NPC inverter is also discussed. The problem of neutral point voltage balancing with its solution is presented. Finally, the simulation and experimental results for three-level NPC inverter are given which validates the proper operation of this topology.